PENENTUAN PATOTIPE VIRUS NEWCASTLE DISEASE (ND) ISOLAT LOKAL PADA UNGGAS DENGAN METODE REVERSE TRANSCRIPTION POLYMERATION CHAIN REACTION DAN RESTRICTION ENDONUCLEASE ANALYSIS (RT-PCR DAN REA) - , Medania Purwaningrum; , Dr.drh. Aris Haryanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Newcastle disease (ND) is a contagious viral disease caused by Avian Paramyxovirus Serotype-1 (APMV-1), species Avian paramyxovirus, genus Avulavirus, family Paramyxoviridae. This viral infection is responsible for devastating outbreak by attacking nerve, respiration, and also digestive system. This disease often followed with decreasing of eggs production and also responsible for economic loss in the poultry industries around the globe. Existing conventional method to identify the patotype of ND virus to differentiate between avirulent and virulent strain was time consuming and expensive. Those reason indicate the necessity to develop a new method to differentiate virulent or avirulent strain of ND virus. The main goal was to differentiate virulent or avirulent strain of ND virus from gene F, which is the virulent marker of ND virus, by RT-PCR and REA method, using 3 restriction enzymes, Hin1L, BamH1, and Apa1. Ten ND virus samples came from Animal Disease Investigation Center (ADIC) Wates virus collection, collected from field case in 2012-2013. RNA of ND virus was collected by extraction from the samples. The product of extraction were used as a template for amplification in RT-PCR. The target of RT-PCR amplification was gene F. In order to amplify this gene, a pair of primer were used (forward 5'-GGAGCCAAACCGCGCACCTGCGG-3' and reverse 5'-GAGGATGTTGGCAGCAT-3'). After the process of RT-PCR, the product then visualized by 1,5% gel agarose electrophoresis on UV transilluminator. The results indicated positive reaction due to existing of DNA fragment band in size of 767 bp. RT-PCR and REA with Hin1l and BamH1 can be used as tool to determine the patotype of ND virus from field specimen. RT-PCR product and REA that showed different restriction pattern were sequenced to get the analysis by using MEGA 5.10 and its restriction pattern map were analyzed by CLC squence viewer 6.8.1. The final result of patotype identification showed similarity between RT-PCR and REA method with sequencing method.